(untitled) (Italian Journal of Public Health, 2004)
The aim of this survey was to study the socio-demographic determinants of drug use in sporting activities at an amateur level in Italy. In 2000 a cross-sectional study was carried out in two Italian regions (Latium and Campania). The participants were 1056 athletes (age range: 16-35 years; 660 males and 396 females). The results show that 28.3% thought “doping” was creatine, 14.7% said racemed amino-acids, 5.8% said proteins, 24.7% did not know and finally 35.7% correctly recognised it as growth hormone. When asked if using drugs was acceptable in order to improve sporting performance, significant results were associated with age (OR = 1.64 for 18-24 years old and OR = 2.22 for 25-30 years old); gender (males were more prone to consider them acceptable); type of sport undertaken (OR = 1.34 for athletes who practice team sport); educational level (athletes with an elementary level education are at higher risk), and knowledge of the effects of anabolic agents (OR = 0.6 for athletes with poor knowledge). The findings of our study confirm the need to implement preventive interventions, with a special focus on healthier behaviour, for reducing factors that encourage the use and the willingness to use licit and illicit drugs.